BAAL/CUP Seminar 2015: Eyetracking as a research method in online language education. (23rd September 2016) - Stickler, Ursula; Shi, Lijing
Abstract : The seminar took place at The Open University, Milton Keynes, United Kingdom, 12–13 June 2015. The objectives of this seminar were to explore the use of eyetracking in advancing online language education, and to provide a platform for the exchange of ideas across disciplines (language, education, and computing). The overarching aim was to lay the foundations for a network to support future eyetracking research collaboration on the practical, methodological and theoretical level.